편마비 환자의 반 쪼그려 앉기(semi-squat)동작 시 양하지 지지면의 형태가 하지 근활성도와 체중분포에 미치는 영향 - 양용필; Yong Pil Yang; 노정석; Jung Suk Roh (Han'guk Chŏnmun Mulli Ch'iryo Hakhoe chi = Journal of the Korean Academy of University Trained Physical Therapists, 2012)
This study used an unstable platform to change the support surface type and position of both lower limbs in order to determine changes in weight distribution and muscle including the vastus medialis, tibialis anterior, lateral hamstring, and lateral gastrocnemius of both lower limbs were evaluated during knee joint flexing and extending in a semi-squat movement in 32 hemiplegic patients. The support platform for both lower limbs; condition 2 had an unstable platform for the non-hemiplegic side and a stable platform for the hemiplegic side; condition 3 had a stable platform for the non-hemiplegic side and an unstable platform for the hemiplegic side; and condition 4 had an unstable platform for both sides. The normalized EMG activity levels of muscles and weight bearing ratio of both sides in the four surface conditions were compared using repeated measures ANOVA. A significant increase was found in the weight support distribution for the hemiplegic side in flexing and extending sessions in condition 2 compared to the other conditions (p<.05). A statistically significant decrease in significant decrease in asymmetrical weight bearing in flexing and extending sessions was observed for condition 2 compared to the other conditions (p<.05). A similar significant decrease was found in differences in muscular activity for both lower limbs in condition 2 (p<.05). The muscular activity of the hemiplegic side, based on the support surface for each muscle showed a significantly greater increase in condition 2 (p<.05). An unstable platform for the non-hemiplegic side and a stable platform for the hemiplegic side therefore increased symmetry in terms of the weight support distribution rate and muscle activity of lower limbs in hemiplegic patients. The problem of postural control due to asymmetry in hemiplegic patients should be further studied with the aim of developing continuous effects of functional training based on the type and position of the support surfaces and functional improvement.